Pengaruh Tingkat Pengungkapan Sustainability Reporting terhadap Earnings Management pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2021–2024 - Hanifa Diah Astari; Susi Handayani (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This study empirically investigates how the degree of transparency in sustainability reporting influences earnings management practices among listed companies in Indonesia's energy sector on the Indonesia Stock Exchange, covering the period from 2021 to 2024. Grounded in three theoretical perspectives Agency Theory, Stakeholder Theory, and Legitimacy Theory this study argues that when companies disclose their sustainability information more comprehensively, management's capacity to manipulate reported earnings becomes increasingly constrained, owing to reduced information asymmetry and heightened external scrutiny. The independent variable is measured through the Sustainability Reporting Disclosure Index (SRDI), constructed based on the GRI Standards 2021, while earnings management is proxied by the absolute value of discretionary accruals derived from the Modified Jones Model. Firm size and leverage are incorporated as control variables. Using purposive sampling, 32 companies were selected, generating a total of 128 observations. The data were analysed through panel data regression employing a Random Effects Model with White's cross-section robust standard errors. The results reveal that sustainability reporting transparency does not exert a statistically significant effect on earnings management. This finding suggests that, within Indonesia's energy sector, sustainability reporting tends to function more as a legitimacy-seeking tool rather than a genuine expression of corporate transparency. Firm size was found to have a significant negative effect on earnings management, whereas leverage did not demonstrate a meaningful influence. This study contributes to the growing body of literature examining the relationship between sustainability reporting and earnings management, with particular relevance to the energy sector in the Indonesian context.